Pengembangan Label Cerdas Kolorimetrik untuk Indikator Kesegaran Lobster Air Tawar dari Film PVA dan Chitosan dengan Ekstrak Kulit Buah Naga Merah - Axiomawan, Firman Yudha; Suyatma, Nugraha Edhi; Arpah, Muhammad (Jurnal Teknologi dan Industri Pangan, 2024)
Crayfish (Cherax quadricarinatus) is an economically valuable fishery product but its freshness and nutritional content decreases quickly during storage. To observe the freshness level of crayfish, a smart label was developed with the addition of color indicators made from red dragon fruit peel extracts (RDFPE). The purpose of this study was to apply RDFPE as an indicator of colorimetric smart labels in monitoring the freshness of crayfish. There were four levels of RDFPE, namely 0, 15, 20, and 25%. When different levels of pH were used, RDFPE colors changed. Optimization using Design Expert (V13) software indicated that the use of 15% (v/v) of RDFPE in PVA and chitosan film was the best treatment for preparing a colorimetric smart label. This smart film had a thickness of 101 mm, tensile strength of 4.4 MPa, elongation of 118%, and water vapor permeability of 4.3x10-10 g s-1 m-1 Pa-1. The pH, total volatile basic (TVB), and total plate count (TPC) values of crayfish rose along with storage time and they had a strong correlation with the ∆E value of the smart label. This study concluded that the addition of RDFPE could be used as a color indicator to fabricate colorimetric smart labels for monitoring the freshness of packaged crayfish.